Congenital malformation of the pulmonary airway (MCVAP), Case Report - Medina Valdivia, José Luis (2020)
Pulmonary malformations include different abnormalities of the respiratory system, including congenital pulmonary airway malformation (MCVAP), formerly known as cystic adenomatous malformation, which is a rare disease with an incidence of 1 in 8,300 to 35,000 live births. Five classification patterns have been described according to the number and size of the cyst, in addition to their histological characteristics, with type 1 MCVAP being the most frequent, showing displacement of adjacent structures according to size, associated with brochioalveolar carcinoma, and good prognosis after resection surgical. We present the case of a four-year-old female patient with recurrent hospitalizations for pneumonia and bronchial obstructive syndrome. The thorough anamnesis and physical examination supplemented with the chest x-ray and tomography allowed the diagnosis to be suspected. Later, the patient underwent surgery, there were no complications and the respiratory symptoms disappeared. The histopathological study confirmed the diagnosis.